The Role of Physical Activity in the Prevention of Cardiovascular Diseases – A Literature Review - Pyjecka, Małgorzata; Kwitowska, Patrycja; Ubysz, Eryk; Muraszewska, Emilia; Muraszewski, Łukasz; Król, Agata; Lewandowska, Edyta; Paczkowski, Maciej; Wręczycki, Mariusz; Łuczyński, Cezary (Quality in Sport, 2026)
Background: Cardiovascular diseases are among the leading causes of morbidity and mortality worldwide. Their development is associated with risk factors such as hypertension, obesity, diabetes, and abnormal lipid profiles. Regular physical activity is recognized as an effective preventive factor that positively influences heart and vascular function and reduces the risk of cardiovascular diseases. Aim: To review the scientific literature on the role of physical activity in preventing cardiovascular diseases. Materials and Methods: A literature review was conducted using PubMed and Google Scholar, covering studies published within the last 10 years. Results: Regular physical activity induces numerous beneficial cardiovascular adaptations. These include improved endothelial function, reduced blood pressure, increased HDL cholesterol, decreased LDL cholesterol, improved insulin sensitivity, reduced inflammation, and body weight management. Physically active individuals demonstrate higher cardiorespiratory fitness, which lowers the risk of coronary artery disease, stroke, and heart failure. Both moderate and vigorous intensity training produce positive metabolic and cardiovascular effects, limiting the development of risk factors. Conclusions: Physical activity is a key element in cardiovascular disease prevention. Evidence indicates that regular exercise benefits both the prevention of cardiovascular conditions and the improvement of cardiovascular function in individuals with existing disorders. The literature highlights physical activity as an effective strategy to reduce cardiovascular risk and enhance overall health.